2012
DOI: 10.1016/j.drugalcdep.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Response inhibition and psychomotor speed during methadone maintenance: impact of treatment duration, dose, and sleep deprivation

Abstract: Background In opiate-dependent individuals, abstinence results in deficits in cognitive functioning, which may be exacerbated by medication-associated sleep disruption. Method To assess cognitive function and the influence of sleep deprivation (SD), 14 healthy control (HC) and 22 methadone maintained (MM) participants completed the Continuous Performance Task (CPT) after a baseline night, a night of total SD, and two recovery sleep nights. The Digit Symbol Substitution Task (DSST) was administered at bedtime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 39 publications
4
28
1
1
Order By: Relevance
“…Longer methadone treatment duration was associated with better performance on some measures (Sternberg working memory, free recall, and metamemory), though false alarm rates during recognition memory were increased. These findings are consistent with past correlational and longitudinal studies showing improved cognitive performance with methadone stabilization (Bracken, et al, 2012; Gruber et al, 2006; Soyka et al, 2008; Soyka, Zingg, Koller, & Hennig-Fast, 2010). In a longitudinal study, Gruber et al (2006) found improved memory and focused attention (DSST), but no change on measures of semantic fluency, psychomotor function (Trail Making Test), or inhibitory control, following two months of treatment compared to the first few weeks of treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Longer methadone treatment duration was associated with better performance on some measures (Sternberg working memory, free recall, and metamemory), though false alarm rates during recognition memory were increased. These findings are consistent with past correlational and longitudinal studies showing improved cognitive performance with methadone stabilization (Bracken, et al, 2012; Gruber et al, 2006; Soyka et al, 2008; Soyka, Zingg, Koller, & Hennig-Fast, 2010). In a longitudinal study, Gruber et al (2006) found improved memory and focused attention (DSST), but no change on measures of semantic fluency, psychomotor function (Trail Making Test), or inhibitory control, following two months of treatment compared to the first few weeks of treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the right IFG is activated not only during response inhibition but also during stimulus-driven attention allocation (Chikazoe et al , 2009). It has been shown that heroin abuse is also associated with deficits in attentional set-shifting (Ornstein et al , 2000) and that opiate-dependent participants actively enrolled in a methadone-maintaining program showed reduced selective attention (Bracken et al , 2012). A recent study explored the cognitive deficits in heroin abusers and showed that the decreased ability to shift attention and inhibit inappropriate response tendencies, which cumulate with years of consumption, may be mediated by dysfunctional IFG activity (Lundqvist, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The patients were dichotomized into those receiving methadone more than 80 mg or less than 80 mg. The 80 mg cut-off was chosen since this is the consensus for high dose and low dose methadone grouping as proposed by previous studies 15 - 17 and our predetermined cut-off using Receiver Operating Curve (ROC) analysis 18 . All ECGs were performed 24 hours after last methadone dose with subjects remained supine for 5 minutes prior to ECG recording.…”
Section: Methodsmentioning
confidence: 99%